Computational approach of alpha and proton interaction of gadolinium bismuth borate glass system using SRIM program. (2022) - Chaiphaksa, W.; Yonphan, S.; Chanthima, N.; Kaewkhao, J.; Sanwaranatee, N.W.
Abstract: The purpose of this research is used to study the alpha and proton shielding characteristics of gadolinium bismuth borate glass with chemical compositions (80-x)B2 O3 : 5CaF2 : 15Bi2 O3 : xGd2 O3 (where ×  = 0, 5, 10, 15, and 20 mol%). The mass stopping power (MSP) and projected range (PR) have been calculated by SRIM program for the proton and alpha particles. From the calculation, it was found that the proton mass stopping power (PMSP) value and alpha mass stopping power (AMSP) values tended to decrease with increasing Gd2 O3 concentration. From the analysis, adding the Gd2 O3 content in the glass affects the structure which increase the alpha and proton shielding properties. Likewise, the values of proton projected range (PPR) and alpha projected range (APR) were found to decrease with increasing Gd2 O3 content. From the analysis, adding the Gd2 O3 content to the glass affect the increase in the alpha and proton shielding properties. These results suggest that gadolinium bismuth borate glass is suitable to develop as alpha and proton shielding materials.